2020
DOI: 10.1155/2020/3573240
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Fraction from Hedyotis diffusa plus Scutellaria barbata Suppresses Migration of Bone‐Metastatic Breast Cancer Cells via OPN‐FAK/ERK/NF‐κB Axis

Abstract: Hedyotis diffusa plus Scutellaria barbata is a couplet of medicinal that has been commonly used to treat inflammation-related diseases and various types of tumors. However, the effect of this couplet on tumor cell migration has not been elucidated. With the aid of MCF-7-BOM, a bone-metastatic subline of ER + breast cancer MCF-7, we showed that ethyl acetate fraction extracted at an equal weight ratio of Hedyotis diffusa plus Scutellaria barbata (EA11) inhibited cell migration of MCF-7-BOM in a concentration-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…HDE may share a similar anticancer mechanism with BIIB021, but further investigation is required. In addition, HDE is extracted from the natural herb Hedyotis diffusa, which has been used for cancer treatment in China for centuries (46). Previous studies have demonstrated that TCHD could induce apoptosis in leukemia cell lines Kasumi-1, KG-1, THP-1, U937 and K562 (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…HDE may share a similar anticancer mechanism with BIIB021, but further investigation is required. In addition, HDE is extracted from the natural herb Hedyotis diffusa, which has been used for cancer treatment in China for centuries (46). Previous studies have demonstrated that TCHD could induce apoptosis in leukemia cell lines Kasumi-1, KG-1, THP-1, U937 and K562 (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the combined use of the two herbs is not simply superimposed, and their combined application is more effective than a single drug [16] . Modern pharmacological studies found that SB plus HD herb pair (SBHD) could induce cancer apoptosis, inhibit cancer cell proliferation, and suppresses cancer cells migration [17][18][19][20] . In recent years, the two herbs and their extracts have been widely used in the treatment of esophageal cancer and have shown remarkable effects [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used as a detoxifying herb in TCM due to its functions of clearing heat, removing toxicity, activating blood and reducing swelling 13 , 14 . Accumulating evidence has proved that HD has anticancer activity in the treatment of both breast cancer and cervical cancer 15 , 16 . HD has been reported to be able to inhibit colorectal cancer growth in vivo and in vitro 17 .…”
Section: Introductionmentioning
confidence: 99%